Practical training report in Cahaya Mata Sarawak Management Service Sdn Bhd / Nur Syahidah Mohamad Naufal - Mohamad Naufal, Nur Syahidah (Universiti Teknologi MARA, Sarawak, 2018)
Cahaya Mata Sarawak Sdn Bhd was established on 8th October 1974 whereby it was the first organization in Sarawak that produced cement. Today, the organization has been listed in Bursa Malaysia as the leading main market of Malaysian stock exchange and has celebrated 44 years of growth as the resource of Sarawak's development in line with the name itself which carry the meaning of 'the lights of Sarawak' as well as their focused vision and mission, To become the PRIDE of Sarawak & Beyond. Moreover, the organization has continuously expand its business involving manufacturing, construction materials, road maintenance, property development, education and other services required in achieving to make Sarawak as developed country by 2030. CMS were also one of the major private sector in Sarawak which operating to support the Sarawak growth towards 2030 through the opportunities provided by Sarawak Corridor Of Renewable Energy (SCORE), which is one of the economic corridor provided by the Federal Government Malaysia with their focus area on the development of rural's. In addition, the organization also actively engage with charity event to focus on raising the fund. Most of the time the employee of CMS will be donating their used cloth, shoes, bags and foods as well as doing CSR annually for such purposes. Other than that, they also organize activities such as charity run for the public to join their team and help those who really in need through the fund they have collected.